2021
DOI: 10.3389/fpsyg.2021.725525
|View full text |Cite
|
Sign up to set email alerts
|

A Curriculum Integrating STEAM and Maker Education Promotes Pupils' Learning Motivation, Self-Efficacy, and Interdisciplinary Knowledge Acquisition

Abstract: Contemporary society expects learners to synthesize large amounts of available information and take advantage of interdisciplinary knowledge to tackle complex, real-world issues. STEAM education aims to cultivate students' ability to solve such problems through interdisciplinary thinking but is often represented by courses that are merely disjointed arrays of school subjects. On the other hand, Maker education harnesses society's enthusiasm for technological innovation and creativity but overlooks the scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
2
16
0
3
Order By: Relevance
“…The creative process was a higher-level understanding of science, and finally built up students' interdisciplinary knowledge. Jia et al (2021) also confirmed the evaluation to the comprehensive STEAM approach to academic performance. STEAM education can not only improve students' ability to conceptualize topics, but also strengthen students' learning and understanding of interdisciplinary knowledge, and promote students' overall academic performance in learning activities.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The creative process was a higher-level understanding of science, and finally built up students' interdisciplinary knowledge. Jia et al (2021) also confirmed the evaluation to the comprehensive STEAM approach to academic performance. STEAM education can not only improve students' ability to conceptualize topics, but also strengthen students' learning and understanding of interdisciplinary knowledge, and promote students' overall academic performance in learning activities.…”
Section: Discussionsupporting
confidence: 63%
“…Each detail should be handled until the final expanded drawing and three-dimensional rendering were completed (Figure 1). Seventh, students presented their final work, and shared the design ideas and the concepts of their work with others (Jia et al, 2021).…”
Section: Courses Fields Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, it is instructive to conceptualise the term "curriculum" before attempting to conceptualise "curriculum design". The conceptual meaning of curriculum explicates an embodiment of knowledge, skills and attitude that are impacted on persons through the school administration system (Jia, Zhou & Zheng, 2021). By "knowledge", is meant the integration of all facts, postulations, philosophies and rules required to be attained for an individual/student to be certified as competent in a chosen area of study.…”
Section: Conceptualising Curriculum and Curriculum Designmentioning
confidence: 99%
“…Creativity often plays key roles in sophisticated processes in engineering design education (Dorst, 2011;Forbes, 2008). Several studies have examined how individuals' creativity is influenced during the design-based learning process (Jia et al, 2021;Khamhaengpol et al, 2021;Ozkan & Topsakal, 2021;Shen et al, 2021). However, instead of examining how individuals creatively designed their works, these studies investigated individuals' creativity through self-report questionnaires (Shen et al, 2021), divergent thinking tests (Ozkan & Topsakal, 2021), or merely the completeness of the products (Jia et al, 2021;Khamhaengpol et al, 2021).…”
Section: Creativity In the Design Processmentioning
confidence: 99%